Word across the water: american protestant missionaries, pacific worlds, and the making of imperial histories - Smith, Tom (The United States in the world, 2024)
"A comparative history of how American missionaries engaged with and interpreted the culture and society of Hawaii and the Philippines in the nineteenth and early twentieth centuries"-